Reciprocal signaling between the ectoderm and a mesendodermal left-right organizer directs left-right determination in the sea urchin embryo. - Nathalie Bessodes; Emmanuel Haillot; Véronique Duboc; Eric Röttinger; François Lahaye; Thierry Lepage (PLoS Genetics)
During echinoderm development, expression of nodal on the right side plays a crucial role in positioning of the rudiment on the left side, but the mechanisms that restrict nodal expression to the right side are not known. Here we show that establishment of left-right asymmetry in the sea urchin embryo relies on reciprocal signaling between the ectoderm and a left-right organizer located in the endomesoderm. FGF/ERK and BMP2/4 signaling are required to initiate nodal expression in this organizer, while Delta/Notch signaling is required to suppress formation of this organizer on the left side of the archenteron. Furthermore, we report that the H(+)/K(+)-ATPase is critically required in the Notch signaling pathway upstream of the S3 cleavage of Notch. Our results identify several novel players and key early steps responsible for initiation, restriction, and propagation of left-right asymmetry during embryogenesis of a non-chordate deuterostome and uncover a functional link between the H(+)/K(+)-ATPase and the Notch signaling pathway.